2022
DOI: 10.1021/acs.joc.1c03058
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interaction- and Steric Effect-Controlled Regiodivergent Selectivity in Dimeric Manganese-Catalyzed Hydroarylation of Internal Alkynes: A Computational Study

Abstract: Selective hydroarylation of internal alkynes catalyzed by a dimeric manganese complex provides a powerful strategy for the construction of multisubstituted alkenes. In this work, density functional theory (DFT) calculations and experimental studies were carried out to explore the mechanism and origin of regiodivergent hydroarylation of internal alkynes reported by our group. The results demonstrate that this reaction first proceeds via a bimetallic mechanism to generate the active catalyst that subsequently un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Regarding the mechanism, it has been recently studied by Yuan, Bi, Xie, and co-workers. 86 In this work they found that the activation step proceeds via a bimetallic mechanism, yielding a monomeric catalytically active species, which subsequently undergoes an alkyne migratory insertion, a protodemetalation, and catalyst regeneration, completing the catalytic turnover. From these, precatalyst activation was identified as the rate-determining step, whereas alkyne migratory insertion was proposed to be mainly responsible for the regioselectivity, which is highly dependent on the steric properties of the species involved.…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondsmentioning
confidence: 92%
See 1 more Smart Citation
“…Regarding the mechanism, it has been recently studied by Yuan, Bi, Xie, and co-workers. 86 In this work they found that the activation step proceeds via a bimetallic mechanism, yielding a monomeric catalytically active species, which subsequently undergoes an alkyne migratory insertion, a protodemetalation, and catalyst regeneration, completing the catalytic turnover. From these, precatalyst activation was identified as the rate-determining step, whereas alkyne migratory insertion was proposed to be mainly responsible for the regioselectivity, which is highly dependent on the steric properties of the species involved.…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondsmentioning
confidence: 92%
“…Regarding the mechanism, it has been recently studied by Yuan, Bi, Xie, and co-workers . In this work they found that the activation step proceeds via a bimetallic mechanism, yielding a monomeric catalytically active species, which subsequently undergoes an alkyne migratory insertion, a protodemetalation, and catalyst regeneration, completing the catalytic turnover.…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondsmentioning
confidence: 99%